Identify the Effective Factors on Justice-Oriented in Attracting, Retaining and Promoting Human Resources and Provide an Appropriate Pattern - Kazemzadeh Hochghan, Mohammad; Najaf Beigi, Reza; Mirsepasi, Nasser; Daneshfard, Karamollah (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to identify the factors affecting justice-oriented in attracting, retaining and promoting human resources and provide a favorable model. Methodology: This study was applied in terms of purpose and qualitative in terms of implementation. The study population was all articles related to the role of justice-oriented in attracting, retaining and promoting human resources in the scientific databases of Magiran, Scopus from 1991-1992 (227 articles) and managers and human resources experts in government organizations in Tehran in 2018-19. The research sample consisted of 40 articles and 15 experts who were selected according to the principle of theoretical saturation and purposive sampling. Data were collected by filing methods and interviews with specialists and their psychometric indices. Content analysis method was used to analyze the data. Findings: The results showed that the effective factors in justice-oriented in all three processes of recruitment, retention and promotion of human resources included both external and internal factors. For the external factor in all three processes of recruitment, retention and promotion of manpower, four dimensions including cultural (5 common indicators for all three processes of recruitment, retention and promotion of human resources), economic (5 common indicators for all three processes), social (4 indicators Common to all three processes) and political (1 common indicator for all three processes) and for the internal factor three dimensions including management of ethics, values ​​and culture (6 common indicators for all three processes), individual (indicators were different and 4 indicators to attract , 3 indicators for maintenance and 6 indicators for upgrade) and internal indicators (indicators were different and 5 indicators for absorption, 5 indicators for maintenance and 5 indicators for upgrade) were identified. In total, 2 factors, 7 dimensions and 48 indicators were identified and based on that, an appropriate model of factors affecting justice-oriented in attracting, retaining and promoting human resources was designed. Conclusion: According to the research findings, the effective factors in justice-oriented in all three processes of recruitment, retention and promotion of human resources included both external and internal factors